Development of an individualized asynchronous sensor-based telerehabilitation program for patients undergoing total knee replacement: Participatory design. (December 2020) - Naeemabadi, MReza; Søndergaard, Jesper Hessellund; Klastrup, Anita; Schlünsen, Anne Philbert; Lauritsen, Rikke Emilie Kildahl; Hansen, John; Madsen, Niels Kragh; Simonsen, Ole; Andersen, Ole Kæseler; Kim, Katherine K; Dinesen, Birthe
Telerehabilitation programs can be employed to establish communication between patients and healthcare professionals and empower patients performing their training remotely. This study aimed to identify patients' requirements after a total knee replacement following a self-training rehabilitation program, leading to the design and development of a telerehabilitation program that can meet the stakeholders' actual needs. System design, development, and testing were conducted in five iterations based on a participatory design approach. Data collection was performed using interviews, observations, prototyping, and questionnaires. It was found that the main barriers facing the existing rehabilitation program were a lack of clear communication, lack of relevant information, and healthcare professional's feedback. The participants emphasized the main themes of communication, information, training, and motivation in the process of design and development. In using the telerehabilitation program, the patients reported a high level of user-friendliness, flexibility, and a sense of security. This study has identified obstacles in the current rehabilitation program and revealed the potential effectiveness of using asynchronous communication and sensor-based technologies by employing participatory design and development. A higher level of portability and flexibility were observed. However, future studies and development are required to investigate the overall usability and reliability of the telerehabilitation program.